Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/metabo12020120
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Twelve Significant Mycotoxin Contamination in Nut-Based Products by the LC–MS/MS Method

Abstract: In this study, a total of 80 peanut butter, hazelnut butter, and chocolate samples were obtained from local markets in Ankara, Turkey. These foods were analyzed for twelve toxicological important mycotoxins, such as aflatoxin B1 (AFB1), aflatoxin B2 (AFB2), aflatoxin G1 (AFG1), and aflatoxin G2 (AFG2); fumonisin B1 (FB1) and fumonisin B2 (FB2); ochratoxin A (OTA); sterigmatocystin (STE); deoxynivalenol (DON); zearalenone (ZON); T-2 toxin (T2); and HT-2 toxin (HT2) by the LC–MS/MS multi-mycotoxin method. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…As an example, a study by Imperato et al [9] revealed a high rate of contamination for hazelnuts and foods containing hazelnuts, imported in Italy from Turkey. Demirhan et al [28] investigated the mycotoxin contamination of nut-based products (e.g., hazelnut butter and chocolate), obtained from local markets in Ankara (Turkey), observing that most samples were contaminated by AFB1 and other mycotoxins. Sterigmatocystin (STE) and its 3-O-methyl derivative (OMSTE) have been also identified in hazelnuts [12].…”
Section: Occurrence Of Mycotoxins In Hazelnutsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, a study by Imperato et al [9] revealed a high rate of contamination for hazelnuts and foods containing hazelnuts, imported in Italy from Turkey. Demirhan et al [28] investigated the mycotoxin contamination of nut-based products (e.g., hazelnut butter and chocolate), obtained from local markets in Ankara (Turkey), observing that most samples were contaminated by AFB1 and other mycotoxins. Sterigmatocystin (STE) and its 3-O-methyl derivative (OMSTE) have been also identified in hazelnuts [12].…”
Section: Occurrence Of Mycotoxins In Hazelnutsmentioning
confidence: 99%
“…Besides structural similarities, STE shares with AFB1 hepatotoxic and nephrotoxic effects, inducing IARC to classify them as a possible human carcinogen (group 2B) [32]. As can be inferred from the existing literature, ochratoxin A (OTA) seems to be greatly diffused in hazelnuts [10,12,22,33], and as a contaminant of hazelnut-based food [28]. Moreover, the presence in hazelnuts of the dechloro analog of OTA, namely ochratoxin B (OTB), has been also reported [12,16].…”
Section: Occurrence Of Mycotoxins In Hazelnutsmentioning
confidence: 99%
“…Currently, conventional analytical approaches used for AFB 1 monitoring in food include advanced instrumental analysis and fast detection techniques. Instrumental analysis methods mainly rely on chromatography-based techniques, such as high-performance liquid chromatography [ 11 , 12 , 13 ] and liquid chromatography–tandem mass spectrometry (LC-MS/MS) [ 14 , 15 , 16 ], because of their high selectivity, excellent accuracy, and reproducibility. However, these analytical procedures have several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the market products available for the detection of aflatoxin focus mainly on chromatography-based ( Er Demirhan and Demirhan, 2022 , Wu et al, 2021 , Sarwat et al, 2022 , Xuan et al, 2019 ) and immunoassay-based ( Li et al, 2021 , Yan et al, 2022 , Wang et al, 2021 ) solutions( Li et al, 2021 , Wang et al, 2021 , Yan et al, 2022 ). Although chromatography is highly sensitive and exhibits a good reproducibility, its detection cost is high, it requires large-scale instruments and professional operators, and the sample pretreatment process is relatively complicated ( Lerdsri et al, 2021 , Xiang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%